A linkage model for the integrated application of intellectual capital management and the EFQM business excellence model: the case of an ISO 9001 certified public R&D organisation - 496777 Kim, Dong-young; Kumar, Vinod; Kumar, Uma; Hwang, Young-ha
PSZJBL